IMPLIKASI PRINSIP MOST FAVOURED NATION DALAM UPAYA PENGHAPUSAN HAMBATAN PEDAGANGAN INTERNASIONAL - Prawitra Thalib (Universitas Airlangga, 2012)
Barriers on international trade is one of the complicated problems, therefore the efforts to eliminate it still have been doing by the countries around the world. Meanwhile the discrimination factor in international trade is one of the most important issue that can hamper trade and economic progress of a country, because discrimination can cause uneven distribution of goods and services which are aimed to prosper the people of a country. Therefore, the equal treatment among countries in international trade or as known as Most Favoured Nation Priciple, is crucial. This principle emphasizes equal treatment in every country so trading activity will be expected the same in any country. This Principle can automatically remove the obstacles that might occur in the international trade, by maximizing the role of the World Trade Organization in the International Trading arena.Key words: Most Favoured Nation, Discrimination, Trade.